Exploring Subjective Difficulty as l2 Explicit Knowledge in Advanced Grammar Exams - Rizqan, Muhammad Dhika Arif (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Perceiving the difficulty tocomplete an exam is possibly diverse for one student with another. Indeed, this kind of difficulty which called as the subjective difficulty is faced by TEFL students in all degrees, including the master students. This study aims to explore the subjective difficulty and its factors which areperceived by the TEFL master students in completing their mid and final term of Advanced Grammar Exams. In these exams, the students are given tasks to identify the (un)grammatical sentences, correct the errors, and provision the rules. Qualitative method is selected to analyze this case by applying questionnaire, documents, and interview to obtain the data. The findings indicated thatmetalanguagewas their main problem. This difficultywas influenced by familiarity towards the tasks in these exams which should be performed by the students.In their admissions, they have had a complete understanding of the technical and non-technical metalanguage terms. However, using and producing metalanguage in order to label and provide grammatical rules required not only understanding but also similar perception between the students and their lecturer. Interestingly, for the students, the use of metalanguage to provision therules which had been broken in ungrammatical sentences was perceived as a new knowledge.